Designing an Individual Ethics Model for Reporting Audit Errors Using a Grounded Theory Approach - Darvishi, Saber; Nouraei, Maryam; Ghanbari, Mehrdad; Mohammadi, Nahid (Business, Marketing, and Finance Open, 2024)
The present study aims to design an individual ethics model for reporting audit errors using a grounded theory approach. This research employed a meta-synthesis method. The qualitative statistical population consisted of articles published between 2018 and 2024. In this study, 279 articles were evaluated, of which 242 articles were excluded in several stages, leaving 37 articles as the final sample of the present study. The results of the statistical analysis were categorized into causal conditions, context, intervening conditions, action strategies, and outcomes. The primary categories of organizational laws and regulations, along with hereditary and acquired personality traits and behaviors, were classified as causal conditions. Supportive regulations and incentives were identified as intervening conditions. The primary category of societal norms and values for reporting errors was categorized under context. The organizational structure of auditing firms and the professional judgment and decision-making of auditors were identified as action strategies. Lastly, moral sensitivity and courage, along with commitment and responsibility, were classified as outcomes.